Effect of pregnancy and correlation of weight and heart rate with electrocardiographic parameters in the American Miniature Horse - B.P. Santarosa; M.L.G. Lourenço; G.N. Dantas; C.M.V. Ulian; M.C.T. Heckler; M.J. Sudano; R.C. Gonçalves; S.B. Chiacchio (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2016)
ABSTRACT There are studies on electrocardiogram (ECG) in several breeds of horses, which highlights the growing importance of cardiology in this species. But few authors have addressed the influence of pregnancy on the cardiac physiology of the mare, and specifically, there are no studies on the Mini-horse breed, as well as no correlation of body weight (BW) and heart rate (HR) with electrocardiographic parameters in this breed. The aims of this study were to determine the effects of pregnancy on ECG parameters and to examine the relationships between these variables and body weight (BW) and heart rate (HR). A total of 203 animals were used, including 143 females (66 pregnant) and 60 males. Electrocardiographic examinations were performed by computerized electrocardiogram (TEB), and the parameters were evaluated in six leads in the frontal plane (Lead I, II, III, aVR, aVL and aVF) and base-apex (BA). BW was inversely proportional to HR, which in turn showed an inverse relationship with the duration of the P-wave and the PR and QT intervals. The P-wave amplitude (lead II) was higher in pregnant animals than in non-pregnant animals. The effect of reproductive status should be monitored by ECG throughout the entire gestational period. The 66 pregnant mares in this study were examined during the first third of their pregnancies, thus, few differences were observed between pregnant and non-pregnant animals.